Case report: Navigating treatment pathways for cardiac intimal sarcoma with PDGFRβ N666K mutation - Nishiyama, Akihiro; Sato, Shigeki; Sakaguchi, Hiroyuki; Kotani, Hiroshi; Yamashita, Kaname; Ohtsubo, Koushiro; Mizuguchi, Keishi; Ikeda, Hiroko; Iino, Kenji; Takemura, Hirofumi; Takeuchi, Shinji (Frontiers in Oncology, 2024)
In the realm of rare cardiac tumors, intimal sarcoma presents a formidable challenge, often requiring innovative treatment approaches. This case report presents a unique instance of primary intimal sarcoma in the left atrium, underscoring the critical role of genomic profiling in guiding treatment. Initial genomic testing unveiled a somatic, active mutation in PDGFRβ (PDGFRβ N666K), accompanied by MDM2 and CDK4 amplifications. This discovery directed the treatment course toward pazopanib, a PDGFRβ inhibitor, following irradiation. The patient's response was remarkable, with the therapeutic efficacy of pazopanib lasting for 16.3 months. However, the patient experienced a recurrence in the left atrium, where subsequent genomic analysis revealed the absence of the PDGFRβ N666K mutation and a significant reduction in PDGFRβ expression. This case report illustrates the complexities and evolving nature of cardiac intimal sarcoma treatment, emphasizing the potential of PDGFRβ signaling as a strategic target and highlighting the importance of adapting treatment pathways in response to genetic shifts.